Publisher Correction: Chalcogenide glass-on-graphene photonics. Issue 3 (March 2018) - Lin, Hongtao; Song, Yi; Huang, Yizhong; Kita, Derek; Deckoff-Jones, Skylar; Wang, Kaiqi; Li, Lan; Li, Junying; Zheng, Hanyu; Luo, Zhengqian; Wang, Haozhe; Novak, Spencer; et al.
In the version of this Article originally published online, the following statement for the equally contributing authors was missing: "Hongtao Lin, Yi Song, Yizhong Huang and Derek Kita contributed equally to this work." This has now been corrected in all versions of the Article.